(untitled) (Global Journal of Management and Business Research, 2017)
Social business is an innovative idea which connects the business and society to eliminate poverty, hunger, unemployment and any other social problems. This study is based on the notion of structural evolution and influence of social business to eradicate the social problems in Bangladesh. This study is conducted based on secondary data and the type of the research is descriptive in nature. The research findings revealed that social business has the significant differences between traditional business and Corporate Social Responsibility (CSR) as well as it has generated a lot of positive social impact like poverty reduction, create employment opportunities, reduce aid dependency, and finally, there is an option to mobilize the private sector resources.